Novel 7-Chloro-(4-thioalkylquinoline) Derivatives: Synthesis and Antiproliferative Activity through Inducing Apoptosis and DNA/RNA Damage - Joyce E. Gutiérrez; Esteban Fernandez-Moreira; Miguel A. Rodríguez; Michael R. Mijares; Juan Bautista De Sanctis; Soňa Gurská; Petr Džubák; Marián Hajdůch; Julia Bruno-Colmenarez; Luis Rojas; Denis Deffieux; Laurent Pouységu; et al. (MDPI AG, 2022)
A series of 78 synthetic 7-chloro-(4-thioalkylquinoline) derivatives were investigated for cytotoxic activity against eight human cancer as well as 4 non-tumor cell lines. The results showed, with some exceptions, that sulfanyl 5-40 and sulfinyl 41-62 derivatives exhibited lower cytotoxicity for cancer cell lines than those of well-described sulfonyl N-oxide derivatives 63-82. As for compound 81, the most pronounced selectivity (compared against BJ and MRC-5 cells) was observed for human cancer cells from HCT116 (human colorectal cancer with wild-type p53) and HCT116p53−/− (human colorectal cancer with deleted p53), as well as leukemia cell lines (CCRF-CEM, CEM-DNR, K562, and K562-TAX), lung (A549), and osteosarcoma cells (U2OS). A good selectivity was also detected for compounds 73 and 74 for leukemic and colorectal (with and without p53 deletion) cancer cells (compared to MRC-5). At higher concentrations (5 × IC50) against the CCRF-CEM cancer cell line, we observe the accumulation of the cells in the G0/G1 cell phase, inhibition of DNA and RNA synthesis, and induction of apoptosis. In addition, X-ray data for compound 15 is being reported. These results provide useful scientific data for the development of 4-thioalkylquinoline derivatives as a new class of anticancer candidates.